Landscape Evolution and Human Settlement in the Iroise Sea (Brittany, France) during the Neolithic and Bronze Age. (30th September 2014) - Pailler, Yvan; Stéphan, Pierre; ,; Gandois, H.; Nicolas, C.; Sparfel, Y.; Tresset, A.; Donnart, K.; Dréano, Y.; Fichaut, B.; Suanez, S.; Dupont, C.; et al.
Abstract : The Molène archipelago appears to be particularly rich in Neolithic and Bronze Age remains and an exceptional concentration of megaliths has been brought to light. Several settlements are confirmed by dry-stone structures or by shell middens. These data give precious indications on the occupation chronology of the area. Moreover they allow us, for the first time in Brittany, to reconstruct everyday life during the late Prehistoric period. A prerequisite to this reconstruction was a better understanding of the evolution of the environment during this period, which locally implies a better knowledge of paleogeographic changes related to Holocene sea-level rise as well as on floral and faunal resources. The results obtained through paleogeographic reconstructions show that the archipelago since 4500bc was already disconnected from the mainland. The megalithic monuments must therefore have been erected and used by islanders present on the archipelago from the middle of the 5th to the 2nd millenniumbc . The distribution of the megalithic tombs reveals landscape occupation strategies which respond to both cultural choices and natural constraints. Throughout the entire period, geographic isolation has continued to increase, although it did not imply strong cultural specificities. Nevertheless, the increasing remoteness of the islands has fostered the search for livelihoods based on the intense exploitation of coastal resources. Despite their focus on the sea, these people did not neglect what inland areas could offer as evidenced by the early agro-pastoral practices in the archipelago. Abstract : In memory of Pierre Arzel, algologist, ethnologist, and shore surveyor RÉSUMÉ: L'archipel de Molène s'avère particulièrement riche en vestiges du Néolithique et de l'Âge du Bronze. Une concentration exceptionnelle de monuments mégalithiques y a été mise en évidence. Plusieurs habitats sont attestés par la présence d'un bâtiment en pierres sèches ou de dépotoirs domestiques riches en faune et en mobilier. Ces données nous renseignent sur la chronologie des occupations du secteur et nous permettent, pour la première fois en Bretagne, d'esquisser le mode de vie des hommes de la Préhistoire récente. Afin de pousser plus loin la réflexion, il nous a paru nécessaire de mieux comprendre l'évolution de l'environnement en contexte insulaire, par de nouvelles recherches sur les variations du niveau marin, corrélées à l'étude du paysage végétal, de la géomorphologie et de la faune. Les résultats issus des reconstitutions paléogéographiques montrent que l'archipel était déjà constitué dès 4500BC . Les monuments mégalithiques de l'archipel sont donc le fait de populations insulaires ayant fréquenté l'archipel sur une longue période, du milieu du Ve jusqu'au IIe millénaireBC . La répartition des sépultures mégalithiques reflète des stratégies d'implantations qui répondent à des choix culturels et à des contraintes naturelles. Durant toute cette période, l'isolement géographique n'a cessé de s'accroître, sans donner lieu pour autant à des particularismes culturels marqués. Néanmoins, l'éloignement croissant des îles a encouragé la recherche de moyens de subsistance basés sur l'exploitation intense des ressources littorales. Tournées vers la mer, ces populations n'ont pas négligé les ressources qu'offraient les zones terrestres, comme en témoigne la précocité des pratiques agropastorales dans l'archipel. ZUSAMMENFASSUNG: Besonders reichhaltige Funde aus dem Neolithikum und der Bronzezeit stammen von der Inselgruppe von Molène. Eine außergewöhnliche Konzentration an Megalithanlagen wurde bereits verzeichnet. Daneben sind, durch ein Gebäude mit Trockenmauerwerk oder durch Siedlungsdepots, die zahlreiche Tierknochenreste und Fundstücke enthielten, mehrere Siedlungen belegt. Diese Daten geben Aufschluss über die zeitliche Abfolge der Besiedlung dieses Gebietes und erlauben– zum ersten Mal in der Bretagne -, die Lebensweise der Menschen in der späteren Vorgeschichte nachzuzeichnen. Um die Überlegungen weiter zu vertiefen, schien es uns notwendig, die Umweltentwicklung im Inselkontext besser zu verstehen. Neue Forschungen zu den Meeresspiegelschwankungen, verbunden mit Untersuchungen zum Pflanzenbewuchs, zur Geomorphologie und zur Fauna sollten dazu beitragen. Die Ergebnisse aus den paläogeographischen Rekonstruktionen zeigen, dass die Inselgruppe bereits ab 4500BC bestand. Die Megalithanlagen waren demnach das Werk von Inselbewohnern, die die Inselgruppe über eine lange Periode hinweg aufsuchten, von der Mitte des 5. bis ins 2. vorchristliche Jahrtausend. Die Verbreitung der Megalithgräber spiegelt Besiedlungsstrategien wider, die von kulturellen Vorlieben und natürlichen Zwängen abhängen. Während dieser ganzen Periode nahm die geographische Isolierung zu, ohne jedoch starke kulturelle Besonderheiten zu prägen. Zumindest hat die zunehmende Entfernung der Inseln vom Festland, die Suche nach Nahrungsquellen, die auf einer intensiven Nutzung der Meeresuferressourcen beruhen, gefördert. Der Nachweis von frühem Ackerbau auf den Inseln zeigt, dass die Landressourcen von diesen meeresorientierten Gruppen nicht vernachlässigt wurden. RESUMEN: El archipiélago de Molène es particularmente rico vestigios Neolíticos y de la Edad de Bronce. En el mismo, se relevó una excepcional concentración de monumentos megalíticos. La existencia de numerosos asentamientos fue confirmada mediante el registro de estructuras de morillos o de vertederos domésticos ricos en fauna y mobiliario. Estos datos, nos indican la cronología de las ocupaciones en el sector y nos permiten, por primera vez, delinear el modo de vida de los hombres la Prehistoria reciente en Bretaña. Con el objetivo de profundizar nuestra reconstrucción, fue necesario estudiar la evolución del ambiente insular. La misma fue llevada a cabo a través de nuevas investigaciones sobre la variación del nivel del mar, en correlación con el estudio de la geomorfología, la flora y la fauna. Los resultados paleo geográficos muestran que el archipiélago ya estaba formado desde el año 4500AC . Los monumentos megalíticos en el archipiélago son el resultado la ocupación humana del mismo durante un largo periodo; esto es, desde mediados del siglo V hasta el II milenoAC . La distribución espacial de las sepulturas megalíticas refleja estrategias de ocupación del espacio que responden a las elecciones culturales y a los limitantes naturales. Durante todo este período, el aislamiento geográfico no dejó de acrecentarse, no obstante, el mismo no dio lugar a particularismos culturales destacables. El alejamiento creciente de las islas motivó la búsqueda de medios de subsistencia fundados en la intensa explotación de los recursos litoraleños. No obstante dicha concentración en el aprovechamiento de los recursos marinos, las poblaciones no despreciaron los recursos que les ofrecían las áreas terrestres interiores, como da cuenta de ello la práctica precoz de actividades agropastoriles en el archipiélago.